A study of emergency peripartum hysterectomy in a tertiary care hospital - Bhaskaran, Jeyamani Janaki; Sengodan, Subha Sivagami; Rangesh, Aiswarya; Murugesan, Praveena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency peripartum hysterectomy is a lifesaving procedure done as a last resort to save mother’s life. This study is to analyse the incidence, maternal characteristics, indications and complications following peripartum hysterectomy. Methods: A retrospective analysis of emergency peripartum hysterectomy cases performed over a period of 3 years from January 2015 to December 2017. Results: During the study period, 82 emergency peripartum hysterectomies were performed giving an incidence of 3.47/1000 delivery. Most of the women belong to the age group of 21-30 years (70.7%) and the women of parity two and three (65.8%). Atonic PPH was the most common indication accounting for 59.8% of cases followed by placenta accreta (19.5%). Conclusions: Emergency peripartum hysterectomy remains a lifesaving procedure. Proper antenatal care, early referral, blood bank facilities and timely decision greatly influences maternal outcome.